THE 2016 EULAR GUIDELINES FOR THE DIAGNOSIS AND TREATMENT OF EARLY ARTHRITIS - E. L. Nasonov (Научно-практическая ревматология, 2017)
Early arthritis, which is frequently defined as undifferentiated arthritis, can be an early stage of rheumatoid arthritis (RA), the first manifestation of a wide spectrum of rheumatic diseases and remain undifferentiated for a long time or end spontaneously. The article discusses new European League Against Rheumatism (EULAR) guidelines for the management of patients with early arthritis, which reflect the past decade's advances in new methods for the diagnosis and treatment of early arthritis primarily as a cardinal RA symptom complex. The guidelines include three general principles and 12 recommendations for the diagnosis and treatment of early arthritis. Special attention is given to the need for early use of methotrexate, monotherapy with the latter is the gold standard for the pharmacotherapy of RA. In conclusion, the paper discusses new evidence for the possibilities of preventing RA in a group of anti-cyclic citrullinated peptide antibodies positive patients with arthralgias.